Little house in the big woods - Wilder, Laura Ingalls, 1867-1957 (Harper & Bros, 1953)
A year in the life of two young girls growing up on the Wisconsin frontier, as they help their mother with the daily chores, enjoy their father's stories and singing, and share special occasions when they get together with relatives or neighbors.